Mitigating the Effect of Trust and Emotional Attachment on the Adversity Quotient: Does Perception of Procedural Justice Matter? - Amiddana Ulin Nuha; Vivin Maharani Ekowati (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2026)
The success of a cooperative in achieving its goals and maintaining organisational sustainability largely depends on its members. One of the key factors influencing this success is the level of trust, emotional attachment, and the members' ability to face challenges. This study aims to examine and analyse the role of trust and emotional attachment on the Adversity Quotient of cooperative members, with procedural justice perception as a mediating variable. This study employs a quantitative research approach, with data collected through questionnaires distributed to cooperative members. The population and sample of the study consist of all 170 active members of the cooperative. Data analysis was conducted using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the assistance of the SmartPLS software. The results indicate that trust and emotional attachment have a positive and significant effect on the Adversity Quotient of cooperative members, and procedural justice perception significantly mediates the relationship between trust, emotional attachment, and Adversity Quotient.